Searches for W′ bosons decaying to a top quark and a bottom quark in proton-proton collisions at 13 TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (Springer Verlag, 2017)
Searches are presented for heavy gauge bosons decaying into a top and a bottom quark in data collected by the CMS experiment at √ s = 13 TeV that correspond to an integrated luminosity of 2.2 and 2.6 fb−1 in the leptonic and hadronic analyses, respectively. Two final states are analyzed, one containing a single electron, or muon, and missing transverse momentum, and the other containing multiple jets and no electrons or muons. No evidence is found for a right-handed W0 boson (W0 R) and the combined analyses exclude at 95% confidence level W0 R with masses below 2.4 TeV if MW0 R MνR (mass of the right-handed neutrino), and below 2.6 TeV if MW0 R < MνR . The results provide the most stringent limits for right-handed W0 bosons in the top and bottom quark decay channel.